Home Based Programs on Promoting Return to Work in The Phase II of Cardiac Rehabilitation After Coronary Artery Bypass Graft - Dewi Nur Fiana; Sunaryo B. Sastradimaja; Dian Marta Sari (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background.:The purpose of this case report is to present the benefit of additional home based inteventionprogram given in cardiac rehabilitation phase II of a 50 year old male vetenarian post coronary artery bypassgraft surgery.Methods: A functional approach with the aim of maximising the potency of return to work was adopted. Homeprograms given in this patient is an additional prescribing of overground walking exercise alongside withsupervised exercise with treadmill.Results: Due to his role, he should handle 14 farm. His work required him to move arround in 500 meters eachfarm and he made significant progress from MET 3.2 to 6.29 within 6 weeks and able return to work 4 weeksafter surgery.Conclusion:This finding indicate that additional home based programs was an effective program to promotepatient’s return to work faster.Keywords: CABG, exercise, home program, return to work.